INDONESIAN ISLAMIC BANK: THE GROWTH OF DEPOSIT - Andi Iswandi (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Islamic banks in Indonesia were born in 1992, but their development has only been rapid since 1998, namely since the amendment to the 1992 banking law, which includes equipment regarding the Islamic banking system in the law. Since then, Islamic banks have grown by an average of 150% per year. The central bank, namely Bank Indonesia, and other groups in the market contributed to significant growth, this was done through outreach programs to the public. In December 2003, the Indonesian Ulema Council, an independent clerical body acting as a fatwa for Islamic banking products and operations, issued a decree that interest is haram. This fatwa leads to a rapid increase in deposits to Islamic banks. Although harsh criticism was launched by some Muslim intellectuals, but the fatwa attracted wide attention and awareness of Muslims, but the fatwa attracted widespread attention and awareness of Muslims in general in Indonesia, which caused discussions about Islamic banking to increase rapidly in every region and region of Indonesia. There are two factors behind the success of Islamic banks in increasing deposits from the market. Apart from that, there are also other factors that contributed to this success, such as a number of academics finding alternatives to the capitalistic and secular economic system which is believed to be the main cause of the 1997-2003 Indonesian economic crisis.